Virtual reality based behavioural learning for autistic children - Chandra Reka Ramachandiran,; Nazean Jomhari,; Shamala Thiyagaraja,; Malissa Maria Mahmud, * (Academic Conferences and Publishing International Limited, 2015)
Autism is a disorder in the growth and development of a brain or central nervous system that covers a large spectrum of impairment, symptoms and skills. The children who are suffering from autism face difficulties in communicating and adapting well in the community as they have trouble in understanding what others think and feel. Therefore, there is a need to design effective e-learning method to ease the communication process and to deliver required knowledge to autistic children. Past researchers have highlighted that a virtual reality based learning environment, a computer simulated environment, can facilitate the learning process among autistic children. It is also recognized that the virtual agent plays an important role in virtual worlds as it eases the communication process between the virtual environment (VE) and children with autism. This research aimed to design an effective learning environment for autistic children by developing a virtual environment prototype using face-to-face interviews and picture exchange communication system (PECS) methodology for data collection which was analysed using quantitative tests. The findings suggest that the toilet virtual environment topped the list for being the most popular learning environment among autistic children for behavioural training. The designed prototype identifies autistic children’s and their parents’ needs and also addresses limitations in an existing virtual environment.